Self-employment in French and Italian law - Tyc, Aneta (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The objective of the article is to analyse legal regulations concerning self-employed activity in force in France and Italy. Given that both countries are characterized by a dualism between subordinated work and self-employment, the author looks at legal constructions that do not easily fit into this division. In addition, she places great importance on discussing the social rights of the self-employed.